Sonority across Languages: - Mohammed Shahedul Haque; Fatema Tuj Jannat (Crossings, 2022)
His paper presents a contrastive perspective on the front monophthongs in Spanish and English. Applying the quantitative contrastive method designed and used in the researchers’ earlier works of 2015 and 2019, we highlight the contrast between Spanish and English front monophthongs from a zonal frame of reference in the oral tact, and proceed to offer insight about the comparative levels of learner stress and difficulty that English speaking learners of Spanish and Spanish speaking learners of English as a foreign language will probably experience while attaining accuracy in the acquisition of their target vowel systems. The facts that English and Spanish front monophthongs are more different than similar (71.43: 28.57) and the acquisition workload is greater (80:50) for Spanish speaking learners of English have been established in this study. In addition, English speaking learners of Spanish will need to generate a greater degree (80:50) of substratum counter influence than Spanish speaking learners of English for the accurate acquisition of their target vowels. Although both types of learners can transfer an equal number of vowel sounds from their L1 inventories, the ratio is not the same (20:50) and the study indicates that English speaking learners of Spanish in general will probably experience a slightly greater degree of articulatory stress in attaining perfection in the pronunciation of the target system.